Restitution, repatriation, and legal and ethical normatives in handling aboriginal human remains in Argentina - Cosmai, Natalia Paola; Folguera, Guillermo; Outomuro, Delia (Acta Bioethica, 2013)
This paper analyzes previous and current practices in handling human remains from aboriginal communities. The cases of three Argentinian museums are analyzed which adopted different practices throughout history: Natural Sciences Museum of La Plata, the Ambrosetti Museum, the Llullaillaco mummies, along with ethical and legal norms. The ultimate goal of the work is to draw attention to topics such as restitution, repatriation and the recognition of the rights of aboriginal peoples.